Digital image correlation approach to cracking and decohesion in a brittle coating/ductile substrate system - Wu, D.J.; Mao, W.G.; Zhou, Y.C.; Lu, Chungsheng (Elsevier BV North-Holland, 2011)
By using a digital image correlation technique, the full/local field strain in a brittle coating/ductile substrate system during tension has been successfully monitored. One of the most important experimental results indicates that the distribution of interfacial shear stress in the segmented coating is antisymmetric about the center, which clarifies several controversial assumptions introduced in theoretical models. Two key mechanical properties of thermal barrier coatings, fracture strength in coating and interfacial adhesion strength, were determined as 35.0 ± 4.6 and 14.1 ± 3.2 MPa, respectively, which are consistent with available experimental data.